2011
DOI: 10.1128/aac.00335-11
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis and Systematic Review of Procalcitonin-Guided Therapy in Respiratory Tract Infections

Abstract: Circulating procalcitonin (PCT) is a biomarker that can be used in diagnosing bacterial infections. We performed a quantitative meta-analysis of available randomized controlled trials to determine whether antibiotic therapy based on PCT measurements alters clinical outcomes and antibiotic use in patients with lower respiratory tract infections. We identified studies through MEDLINE (1996 to 2010), the ISI Web of Knowledge (1996 to 2010), and Ovid. Studies that met our criteria were prospective, randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 33 publications
0
29
0
3
Order By: Relevance
“…As PCT levels increase upon bacterial infection and decrease upon recovery, they can be used to guide antibiotic therapy in individual patients as a surrogate biomarker [25,26]. Highly sensitive PCT assays are needed to reliably diagnose CAP and non-CAP lower respiratory tract infections (RTIs) [1,17].…”
Section: Clinical Usefulness Of Pct In Infectious Diseasesmentioning
confidence: 99%
“…As PCT levels increase upon bacterial infection and decrease upon recovery, they can be used to guide antibiotic therapy in individual patients as a surrogate biomarker [25,26]. Highly sensitive PCT assays are needed to reliably diagnose CAP and non-CAP lower respiratory tract infections (RTIs) [1,17].…”
Section: Clinical Usefulness Of Pct In Infectious Diseasesmentioning
confidence: 99%
“…It is important to prevent unnecessary use of antibiotics for the patients, to apply appropriate treatments and to reduce morbidities, mortalities and expenditures for care via performing differential diagnoses of these diseases (7, 8). …”
Section: Introductionmentioning
confidence: 99%
“…These antibiotic-resistant infections increase hospital length of stay, mortality, and hospital costs [41]. A meta-analysis published in 2011 with eight studies (3431 patients) showed a significant reduction in antibiotic prescription in the PCTguided antibiotic treatment groups [42]. However, one should keep in mind that all patients should be carefully and frequently reassessed to ensure that their clinical condition improves spontaneously in a clinically appropriate time.…”
Section: Discussionmentioning
confidence: 98%